Population evacuation: evaluating spatial distribution of flood shelters and vulnerable residential units in Dhaka with geographic information systems - Masuya, Akiko; Dewan, Ashraf; Corner, Robert (Springer Netherlands, 2015)
The objective of this study was to evaluate the spatial distribution of flood shelters in relation to flood hazards in a resource-poor country. Flood hazard estimates were developed from multi-temporal flood-affected frequency and floodwater depth maps. It is intended that the results could support non-structural flood management. In addition, the location of vulnerable housing units was mapped and their accessibility to shelters was computed with the aid of spatial techniques using a geographic information system. A subset of the Dhaka Metropolitan Development Plan zone and Dhaka megacity, covering an area of 878 km2, was used as a case study since this area is likely to experience more frequent and intense flooding in coming years as a result of rapid urbanisation and climatic change. Using three different criteria, the study identified that a total of 5537 buildings, out of 6342 candidate structures, can be used as emergency shelters during floods, and approximately 145,000 dwellings (19.3 % of total residential units) of various types were located in places that are prone to flood. Further, many (3500 of 5537) of the identified shelters were not sufficiently close to vulnerable dwellings to protect approximately 496,000 potential flood victims during an emergency. There were 26.4 % of the total residents living in vulnerable housing units. In addition, 1098 flood shelters were distributed over five catchments in the study area, although in close proximity to vulnerable residents, do not have the capacity to house the number of people who could potentially seek refuge there. This study, the first of its kind in Dhaka, can assist urban planners and emergency managers in developing an effective evacuation plan for an imminent flood disaster as the city currently lacks any disaster management plan.